A stereocontrolled synthesis of (+)-saxitoxin - Bhonde, Vasudev R. (2011)
A concise stereoselective total synthesis of (+)-saxitoxin is described. A silver-(I)-initiated hydroamination cascade constructs the bicyclic guanidinium ion core from a propargyl-bis-guanidine. This sequence creates 2 C-N bonds, 1 C-O bond, and three rings as a single stereoisomer in a single synthetic transformation. This process enabled us to complete the synthesis of (+)-saxitoxin in 14 steps from N-Boc-L-serine methyl ester.